Notes about Theater of the Oppressed in Brazilian universities: Possibilities and impasses (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
The article presents reflections about the relationship between the Theater of the Oppressed (TO) and Brazilian universities. After a brief historical overview, it followed a dialectical approach in order to discuss the implications of the presence of TO in the Brazilian academic environment. Considering the literature and the voices of several researchers, it was pointed out the impasses and the possibilities that emerge from the presence of a militant artistic practice in the Brazilian university environment.
Keywords: Theater of the Oppressed; university; Augusto Boal; dialectics; political theater - Brazil